Hubungan Layanan Bimbingan Karir Dengan Motivasi Lanjut Studi Ke Perguruan Tinggi - Sinta, Neng Siti; Herawati, Endang Sri Budi (Jurnal Eksplorasi Bimbingan dan Konseling, 2023)
The low motivation of students to continue their studies to tertiary institutions is due to the lack of encouragement from close people. BK teachers have a big role in motivating students. Through career guidance, motivated students determine the choice of further study. This study is aimed at finding out the relationship of career guidance services to the further motivation of students studying at SMA Negeri 1 Sindangwangi Majalengka. This research is a quantitative research with correlational methods. The sample in this study were 123 students who were taken randomly from the population of class XII students as many as 186. The results showed that there was a positive relationship between career guidance kites and motivation to continue their studies to college.